Allocating Federal Funds for Science and Technology. (Online access: National Academy of Sciences National Academies Press., 1995)
A report developed from National Academy of Engineering workshops on high-technology small industries compares and contrasts computer, environmental, sporting, and medical companies. The study examines the role of these companies in the US economy, and related public policy issues, focusing on opportunities in the marketplace and governmental nurturance. Contains appendices of comparative tables, but lacks an index and bibliography. Annotation copyright by Book News, Inc., Portland, OR.